The role of the auditor in measuring social and environmental performance indicators in light of the implementation of the GRI standards: (Applied research at the Iraqi General Cement Company) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
This study measures the indicators of social and environmental performance of the contents of the administration's prepared reports on its social and environmental performance by comparing the actual performance with the indicators set within the standards of the Global Reports Initiative (GRI), In preparing this research, the researchers relied on studying the criteria of the Global Reporting Initiative, which aims to achieve a high level of performance disclosure under sustainability, In light of contemporary global trends towards achieving sustainable development and its disclosure and the orientations of economic institutions and units in different countries towards emphasizing the extent of commitment during practicing its activities to achieve sustainability in its dimensions (institutional, economic, environmental and social), In addition to the emergence of studies that emphasized the need for expansion in the areas of disclosure and performance measurement in the light of sustainability towards achieving transparency and developing accountability, the auditing profession is no longer limited to the financial function mainly to verify its integrity and credibility, but it has become obligatory for its practitioners to take into account contemporary developments in the fields Profession to include work on providing other services, which are non-financial services, including performance measurement services and confirmation services for management reports prepared in accordance with sustainability under the application of the standards (GRI), In light of this, the social and environmental performance of the Cement Company was measured to verify its safety and adequacy in accordance with the standards of the Global Reports Initiative (GRI(.The researchers reached a set of conclusions, the most important of which are: (1) The absence of accredited measurement indicators for auditors used for the purpose of verifying the consideration of sustainability when performing business and operational activities. (2) The overall assessment rate for the environmental part was (6%), while the evaluation rate was the total for the social part (4%), which indicates a very low evaluation rate for the disclosure of information related to those parts. (3)The total percentage when performing the level of performance and disclosure according to the environmental and social parts reached (5%) for the three years subject to examination, which indicates a lack of transparency in the disclosure compared to the activity of the economic unit subject to the examination, which is considered an environmental pollutant and thus its reflection on the ability to achieve sustainable development.